2018
DOI: 10.1002/slct.201801732
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Nanoparticulate ZrxTi1‐xO2 Coatings with Controlled Homogeneity of Elemental Composition

Abstract: The mixed oxide ZrxTi1‐xO2 nanoparticulate photocatalysts of different compositions (0≤x≤1) were prepared via sol‐gel method in a rapid micromixing reactor followed by chemical colloid deposition on borosilicate glass beads, drying and heat treatment at temperatures between 400 to 650 °C. The point‐like reaction conditions in the regime of low Damköhler numbers resulted in nucleation of size‐selected reactive zirconium‐titanium oxo‐alkoxy (ZTOA) nanoparticles from zirconium (IV) propoxide and titanium (IV) iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…5). Except for the very beginning related to the photoinduced charges thermalisation, the both curves follow the power-law decay I=At -k , which has been previously related to the relaxation of a series of localised states observed via transient absorption spectroscopy [48] and later attributed to the liberation of charges from shallow traps (Ei) of the Urbach tail (EU) to the conduction band (Eg) with power constant k expressed as k=kBT/Ei [49], where Eg, EU and Ei are band gap, Urbach and trap states energies, kB is Boltzmann constant and T is ambient temperature. According to our measurements, the decay constants of the both materials were very similar and correspond to Eg-Ei  70 meV, which is twice larger than EU at room temperature [50].…”
Section: Resultsmentioning
confidence: 73%
“…5). Except for the very beginning related to the photoinduced charges thermalisation, the both curves follow the power-law decay I=At -k , which has been previously related to the relaxation of a series of localised states observed via transient absorption spectroscopy [48] and later attributed to the liberation of charges from shallow traps (Ei) of the Urbach tail (EU) to the conduction band (Eg) with power constant k expressed as k=kBT/Ei [49], where Eg, EU and Ei are band gap, Urbach and trap states energies, kB is Boltzmann constant and T is ambient temperature. According to our measurements, the decay constants of the both materials were very similar and correspond to Eg-Ei  70 meV, which is twice larger than EU at room temperature [50].…”
Section: Resultsmentioning
confidence: 73%
“…A competition between an increase in the specific surface area and a decrease in the activity per adsorption site has been also confirmed in the compounds with W content ≤ 6 mol% [81]. However, the elemental composition can greatly affect the specific surface area of these materials, as it has been shown in an example of Zr x Ti 1−x O 2 nanopowders [23]. This offers an opportunity to control adsorption and photocatalysis processes in the same material.…”
Section: Introductionmentioning
confidence: 63%
“…The decay curves of the photoinduced charges in pure and W-doped TiO 2 nanopowders are shown in Figure 11. The observed signal has been previously attributed to the liberation of charges from shallow traps with binding energy E * following a power law decay I = At α with parameter α = k B T/E * , where k B is the Boltzmann constant and T is temperature [23]. The shallow states have attracted much attention over the last decade because of their key influence on the photocatalysts' activity [98,99].…”
Section: Synergy Of Adsorption and Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important characteristic showing potentiality of the material application in the photocatalytic process. It can be shown that for a relatively small mass and first order process kinetics,  is proportional to the reaction rate constant R normalized on the photocatalyst mass [Cheng et al 2018;Bouslama et al 2012]. This normalized rate reflects the material effectiveness when the photocatalyst mass is relatively small and decreases at the larger masses due to the saturation of light absorbance in accordance with the Beer-Lambert law.…”
Section: Resultsmentioning
confidence: 99%